Aminopeptidase N purified from gypsy moth brush border membrane vesicles is a specific receptor for Bacillus thuringiensis CryIAc toxin. - Lee, M K (1996)
We have evaluated the binding of Bacillus thuringiensis Cry toxins to aminopeptidase N (APN) purified from Lymantria dispar (gypsy moth) brush border membrane vesicle (BBMV). CryIAc toxin bound strongly to APN, while either the structurally related CryIAa and CryIAb toxins or CryIC, CryIIA, and CryIIIA toxins showed weak binding to APN. An in vitro competition binding study demonstrated that the binding of CryIAc to L. dispar BBMV was inhibited by APN. Inhibition of short circuit current for CryIAc, measured by voltage clamping of whole L. dispar midgut, was substantially reduced by addition of phosphatidylinositol-specific phospholipase C, which is known to release APN from the midgut membrane. In contrast, addition of phosphatidylinositol-specific phospholipase C had only a marginal effect on the inhibition of short circuit current for CryIAa. These data suggest that APN is the major functional receptor for CryIAc in L. dispar BBMV. A ligand blotting experiment demonstrated that CryIAc recognized a 120-kDa peptide (APN), while CryIAa and CryIAb recognized a 210-kDa molecule in L. dispar BBMV. In contrast, CryIAa and CryIAb bound to both the 120- and 210-kDa molecules in Manduca sexta BBMV, while CryIAc recognized only the 120-kDa peptide. The 120-kDa peptide (APN) in L. dispar BBMV reacted with soybean agglutinin, indicating that N-acetylgalactosamine is a component of this glycoprotein.